2018
DOI: 10.1097/mop.0000000000000579
|View full text |Cite
|
Sign up to set email alerts
|

What is new in perinatal HIV prevention?

Abstract: The findings from the IMPAACT PROMISE trial as well as other recent trial and observational findings suggest that while progress has been steady in reducing PMTCT worldwide, the goal of virtual elimination of pediatric HIV worldwide will require careful attention to optimizing safety of new regimens which are less dependent on maternal daily ART adherence and safer in preventing certain toxicities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…57 However, prospective studies are needed regarding the safety, efficacy, and acceptability in women living with HIV before it can be incorporated into perinatal guidelines and practice. 58 Further, perinatal transmission rates have dramatically decreased from one in three newborns infected to less than one in a hundred, 35,59 with elimination of mother to child transmission of HIV in a growing number of countries worldwide. 9 However, gaps remain, in that 1. interventions appear promising as strategies to improve adherence.…”
Section: Infant Feeding Practicesmentioning
confidence: 99%
“…57 However, prospective studies are needed regarding the safety, efficacy, and acceptability in women living with HIV before it can be incorporated into perinatal guidelines and practice. 58 Further, perinatal transmission rates have dramatically decreased from one in three newborns infected to less than one in a hundred, 35,59 with elimination of mother to child transmission of HIV in a growing number of countries worldwide. 9 However, gaps remain, in that 1. interventions appear promising as strategies to improve adherence.…”
Section: Infant Feeding Practicesmentioning
confidence: 99%
“…Mothers are usually commenced on anti-retroviral therapy (ART) as soon as a diagnosis is made. The use of ART allows breastfeeding to commence and continue with all of the advantages this brings to mother an infant [51]. Breastfeeding should be exclusive until six months before any other fluids or complementary foods are given.…”
Section: Hiv Infectionmentioning
confidence: 99%
“…Until now, it was considered that HIV can be transmitted from the mother not only during pregnancy or during birth but also through breastfeeding. Research has shown that the administration of antiretroviral drugs to mothers and babies can signifi cantly reduce the risk of HIV transmission through breastfeeding 39,40 . Th e rate of postnatal transmission of HIV from mother to fetus when the mother is receiving antiretroviral treatment was estimated at 3.5% at 6 months and 4.2% at 12 months 41,42 .…”
Section: Human Immunodeficiency Virus (Hiv) Infection In the Mothermentioning
confidence: 99%